2013
DOI: 10.1017/s0025315413001008
|View full text |Cite
|
Sign up to set email alerts
|

Differential rates of killer whale attacks on humpback whales in the North Atlantic as determined by scarification

Abstract: As in other populations of killer whales, Orcinus orca, prey selectivity in the North Atlantic population may indicate behaviourally or ecologically distinct types of killer whales. Some killer whale ecotypes are known to prey on large whales, but the ecological impact of such predation events is unknown. Since killer whale attacks on humpback whales, Megaptera novaeangliae, are rarely witnessed, resultant scars may be used to determine the frequency of non-fatal predatory interactions. Using images from the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
(50 reference statements)
3
17
0
Order By: Relevance
“…McCordic et al . () reported significant differences in tooth‐rake marks among populations of humpbacks sampled from five different feeding grounds in the North Atlantic, and because nearly all North Atlantic humpbacks breed in the West Indies, they concluded that attacks probably occurred either during migration or on the feeding grounds. When Steiger et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McCordic et al . () reported significant differences in tooth‐rake marks among populations of humpbacks sampled from five different feeding grounds in the North Atlantic, and because nearly all North Atlantic humpbacks breed in the West Indies, they concluded that attacks probably occurred either during migration or on the feeding grounds. When Steiger et al .…”
Section: Discussionmentioning
confidence: 99%
“…From this it was concluded that calves were probably attacked mainly while en route to high-latitude feeding grounds during their first migration (Clapham 2000(Clapham , 2001Mehta et al 2007). McCordic et al (2014) reported significant differences in tooth-rake marks among populations of humpbacks sampled from five different feeding grounds in the North Atlantic, and because nearly all North Atlantic humpbacks breed in the West Indies, they concluded that attacks probably occurred either during migration or on the feeding grounds. When Steiger et al (2008) analyzed tooth rake marks on humpbacks in the eastern North Pacific, they concluded that calves were attacked mainly on the breeding grounds.…”
Section: Where Do Attacks Occur?mentioning
confidence: 99%
“…Although other less exposed parts of the body might also be scarred, they are less visible and thus more difficult to evaluate. Rake marks on humpback whale flukes and on other baleen whales caused by killer whale attacks have been confirmed in different parts of the world (Mehta et al 2007, Steiger et al 2008, Reinhart et al 2013 and are considered to be evidence of unsuccessful or non-lethal attacks (Dolphin 1987, Clapham 2001, Naessig & Lanyon 2004, Mehta et al 2007, Steiger et al 2008, McCordic et al 2014. It is not possible to establish the impact of killer whale predation on humpback whale populations based on such scars because scarred whales are survivors of unsuccessful attacks.…”
Section: Introductionmentioning
confidence: 99%
“…The overall proportion of animals with bent dorsals was calculated by dividing the number of animals with bent dorsals by the total number of cataloged animals. The 95% confidence intervals (CIs) were calculated using the adjusted Wald method for a binomial estimate of the proportion (Lewis & Sauro, 2006;McCordic et al, 2014). The use of the adjusted Wald method for calculating the CIs of proportions from a small sample allows for the derivation of CIs for a binomial estimate of the proportion rather than presenting just a single point estimate (Agresti & Coull, 1998;Lewis & Sauro, 2006).…”
Section: Methodsmentioning
confidence: 99%